2020
DOI: 10.30997/jhd.v6i2.2819
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Serikat Pekerja Dalam Membentuk Perjanjian Kerja Bersama Sebagai Hubungan Kerja Ideal Bagi Pekerja Dengan Pengusaha

Abstract: Jenis Perjanjian kerja di dalam Undang-Undang No. 13 Tahun 2003 Tentang Ketanagakerjaan terdiri dari perjanjian kerja waktu tertentu (PKWT), perjanjian kerja waktu tidak tertentu (PKWTT), dan perjanjian kerja bersama (PKB). Untuk jenis PKWT dan PKWTT dibuat antara pengusaha dengan pekerja, sedangkan PKB perjanjian kerja dibuat berdasarkan kesepakatan antara serikat pekerja dan pengusaha. Tujuan dibentuknya Serikat Pekerja dalam suatu perusahaan untuk membantu pekerja mengaspirasikan kebutuhannya untuk disampai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
0
0
3
Order By: Relevance
“…This indicates that the employment agreement offered by PT Sunwoo Garment Indonesia has represented the application of the applicable law to workers, which in writing can be concluded that legal protection can be guaranteed and workers can easily get their rights. The existence of new worker rights will be given to workers if it is by the agreement of the parties between the worker and the company and the worker performs his obligations as agreed upon (Nita & Susilo, 2020). Regarding obligations, workers must obey the rules set by the company, if they do not obey this means that workers are not carrying out their obligations as workers, if workers have obeyed the rules and are disciplined at work, it will benefit the company and workers because they see the performance of workers being able to provide an increase (Gunawan & Suci, 2022).…”
Section: Implementation Of Law No 6 Of 2023 On Employment Agreements ...mentioning
confidence: 99%
“…This indicates that the employment agreement offered by PT Sunwoo Garment Indonesia has represented the application of the applicable law to workers, which in writing can be concluded that legal protection can be guaranteed and workers can easily get their rights. The existence of new worker rights will be given to workers if it is by the agreement of the parties between the worker and the company and the worker performs his obligations as agreed upon (Nita & Susilo, 2020). Regarding obligations, workers must obey the rules set by the company, if they do not obey this means that workers are not carrying out their obligations as workers, if workers have obeyed the rules and are disciplined at work, it will benefit the company and workers because they see the performance of workers being able to provide an increase (Gunawan & Suci, 2022).…”
Section: Implementation Of Law No 6 Of 2023 On Employment Agreements ...mentioning
confidence: 99%
“…Hak-hak pekerja di dalam perusahaan seharusnya dicantumkan dengan jelas dalam PKB. Dalam pembuatan PKB, peran serikat sangat penting; oleh karena itu, dibutuhkan seorang negosiator yang mempunyai kecakapan, pengetahuan, wawasan yang luas, dan jiwa kepemimpinan (Nita & Susilo, 2020). Tujuan dan fungsi serikat yang sesuai dengan Undang-Undang Nomor 21 Tahun 2001 tentang Serikat Perkeja/Buruh.…”
Section: Penyampaian Materi Kepemimpinanunclassified
“…SP juga dapat mewakili pekerja dalam membuat Perjanjian Kerja Bersama (PKB) yang mengatur hak-hak dan kewajiban pekerja dengan pengusaha melalui suatu kesepakatan umum yang menjadi pedoman dalam hubungan industrial. Dalam perumusan PKB diperlukan peranan dan persetujuan dari perwakilan pekerja yang dalam hal ini diwakili oleh serikat pekerja untuk memuat hak-hak serta kewajiban dasar yang tercantum dalam undang-undang maupun yang tidak tercantum dalam undang-undang namun dapat memberikan keuntungan bagi pekerja (Nita & Susilo, 2020).…”
Section: Hasil Dan Pembahasan Perlindungan Hukum Terhadap Upah Pekerj...unclassified